Women's education in West Nusa Tenggara: an exploration of educational materials and gender equality - Muhammad, Muhammad; Nurhilaliati, Nurhilaliati (Nadwa: Jurnal Pendidikan Islam, 2023)
Women's education within families plays a crucial role in shaping the perception of the ideal woman in society. This study explores female education within the Sasak, Samawa and Mbojo (Sasambo) tribes in West Nusa Tenggara. A descriptive qualitative approach using phenomenology is used in the research. Data were obtained through in-depth interviews, observations, and documentary studies that involved cultural/community leaders and several female community members aged at least 18 years. The results of this study indicate that the educational materials in the three tribes reveal the significant impact of local culture in determining the educational methodology employed. Though each tribe's education features varying elements, they all express cultural, traditional, and religious values in their approach. However, in terms of gender equality and equity, several noteworthy limitations to women's education were revealed in these three tribes. These encompass customary expectations linked to women, societal restrictions that curtail women's autonomy and liberty, and gender responsibilities that do not grant equitable options for women. To address these challenges, the research proposes various actions, including fostering educational programmes that enhance the empowerment of women, encouraging more flexible sharing of roles, respecting women's educational and career choices, and educating on gender equality and justice.